2015
DOI: 10.1007/s10811-015-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical response of Dunaliella salina to cadmium pollution

Abstract: The present study investigates the growth of Dunaliella salina as influenced by cadmium (Cd) contamination. Growth was measured in terms of cell number and chlorophyll a content and was found to decrease with increasing Cd concentration. This metal, which was mainly removed by bioadsorption to cell surfaces (95.34± 3.04 % of total Cd removed), also drastically reduced the soluble and insoluble carbohydrate (0.41±0.01 and 0.81±0.07 pg cell −1 , respectively, for 150 mg Cd L −1 ) concentrations and increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…Wan and Zhang, 2012 reported that the presence of green fluorescent deposits suggests the effect of Cd(II) on vesicular trafficking and/or transport of Cd(II) into vacuoles. Accumulation of the green fluorescence in these deposits may result from the production of beta-carotenes as already described in the algae under a stressor (Shariati and Yahyaabadi 2006;Belghith et al 2015). Thus, the appearance of deposits in the green spectral region could be attributed to chloroplast-related pigments of the photosystem, such as carotenoids, and/or to oxidative metabolic changes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Wan and Zhang, 2012 reported that the presence of green fluorescent deposits suggests the effect of Cd(II) on vesicular trafficking and/or transport of Cd(II) into vacuoles. Accumulation of the green fluorescence in these deposits may result from the production of beta-carotenes as already described in the algae under a stressor (Shariati and Yahyaabadi 2006;Belghith et al 2015). Thus, the appearance of deposits in the green spectral region could be attributed to chloroplast-related pigments of the photosystem, such as carotenoids, and/or to oxidative metabolic changes.…”
Section: Discussionmentioning
confidence: 61%
“…An excess of transition metal ions in the environment may also significantly alter the ultrastructure, increase or decrease growth, chlorophyll content, protein and the antioxidant activities within cells (Sacan et al 2007;Taha et al 2012;Visviki and Rachlin 1994;Wikfors et al 1991). Some of the expressed proteins may be related to temporary storage and the carrier function of chlorophyll and its late precursors, as well as to its antioxidant and photoprotective functions (Belghith et al 2015;Damaraju et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHRs and PCPs-induced oxidative stress exerts an impact on pigments such as chlorophylls and carotenoids. It was previously reported that the exposure to metals caused a decrease in chlorophyll content [279,280,281], with the formation of chlorophyll derivatives [281] and increase in carotenoid content [279,282,283] in microalgal biomass, although the stimulation of chlorophyll synthesis at low metal concentrations was also reported [283]. Literature data gathered regarding the influence of PHRs and PCPs show the decreasing/increasing effects on both chlorophylls and carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Как установлено ранее [Fu, Bell, 2003], снижение солености сопровождается уменьшением содержания катионов натрия и кальция в клетке, вызывая нарушение процесса потребления фосфора и азота микроводорослями и, как следствие, их недостаток для нормальной жизнедеятельности организма. Кадмий также приводит к изменению внутриклеточного ионного состава, так как замещает кальций и цинк в метаболических путях [Andosch et al, 2012]. По-видимому, сочетание пониженной солености с загрязнением кадмием приводит к синергическому эффекту.…”
Section: результаты и их обсуждениеunclassified